Umanization in the Pediatric Intensive Care Unit: facilities and difficulties of the nursing team (Research, Society and Development, 2021)
Objective: To understand the facilities and difficulties of the nursing team in providing humanized care in the Pediatric Intensive Care Unit. Methodology: Descriptive and exploratory qualitative research in the second half of 2021 in the Pediatric Intensive Care Unit of a Hospital in southern Brazil. 17 professionals from the nursing team participated. Data collection was carried out through semi-structured interviews. Data were analyzed using the Thematic Analysis technique. Results: They cited the reduced number of patients in the sector, multidisciplinary teamwork, good remuneration and good communication with the leadership, collaboration and commitment of the team and having a toy library in the hospital as facilities to ensure humanized care. As difficulties mentioned, some mentioned that they do not exist, little time and lack of professionals, work overload, living with the country of hospitalized children, lack of space and comfort for parents in the unit, providing more care technical and mechanistic assistance and the individual difficulties of each person in working with children in critical condition. Conclusion: The humanization of care is part of the concern of professionals working in the unit. The nursing team considers humanized practice to be important, facing challenges in caring for critically ill children and their families.